Economic Insights into Marketing Strategy for Sustaining Competitiveness at UD Yasiira Company - Bawanti, Ni Kadek Yunisa; Adnyana, I Putu Agus (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the marketing strategies implemented by UD Yasiira in maintaining its existence in the midst of increasingly competitive business competition, especially in the school and office supplies sector. This study uses a qualitative approach with data collection techniques through interviews, observations, and documentation of UD Yasiira owners and employees. The results of the study show that UD Yasiira implements four main strategies, namely: (1) customer loyalty, by building long-term relationships through personal service and intense communication; (2) digital marketing, utilizing social media such as Instagram and WhatsApp for promotion and customer interaction; (3) customer relationship management (CRM), through the management of customer data and personalized services; and (4) building customer trust, by maintaining product quality and service transparency. This strategy is considered effective in maintaining customer satisfaction and loyalty, as well as encouraging sustainable business growth. With a combination of differentiation approach and cost leadership, UD Yasiira is able to increase competitiveness and maintain its existence as an MSME in the digital era. This research is expected to be a reference for business actors in developing adaptive and customer-oriented marketing strategies.